Conjugal Transfer but Not Quorum-Dependent tra Gene Induction of pTiC58 Requires a Solid Surface - Piper, Kevin R. (American Society for Microbiology, 1999)
Donors of Agrobacterium tumefaciens harboring a transfer-constitutive derivative of the nopaline-type Ti plasmid pTiC58 transferred this element at frequencies 3 to 4 orders of magnitude higher in matings conducted on solid surfaces than in those conducted in liquid medium. However, as measured with a lacZ reporter fusion, the tra genes of the wild-type Ti plasmid were inducible by opines to indistinguishable levels on solid and in liquid medium. Donors induced in liquid transferred the Ti plasmid at high frequency when mated with recipients on solid medium. We conclude that while formation of stable mating pairs and subsequent transfer of the Ti plasmid is dependent on a solid stratum, the regulatory system can activate tra gene expression to equivalent levels in liquid and on solid surfaces.